Common Vaccine Myths - Kelley Lobean McKinley; Meghan A. Berryman; Melissa K. Jones; Jennifer C. Drew (EDIS)
In this publication, five of the most common vaccine myths are discussed and dispelled. Written by Kelley Lobean McKinley, Meghan A. Berryman, Melissa K. Jones, and Jennifer C. Drew, and published by the UF/IFAS Department of Microbiology and Cell Science, March 2022.